Intestinal Obstruction Caused by Ileocolic and Colocolic Intussusception in an Adult Patient with Cecal Lipoma - Casiraghi, Tiziana (Case Rep Surg, 2016)
Introduction. Intussusception is a rare clinical entity in adults (<1% of intestinal obstructions). Colonic intussusception is even rarer, particularly when caused by lipomas. Case Presentation. A 47-year-old woman presented to our emergency department complaining of abdominal pain with vomiting and diarrhoea. X-ray and CT showed bowel obstruction due to ileocolonic and colocolonic intussusception; a giant colonic lipoma (9 × 4 × 4 cm) was recognizable immediately distally to the splenic flexure of the colon. The patient underwent emergency laparotomy and right hemicolectomy. Assessment of the resected specimen confirmed the diagnosis of giant colonic polypoid lesion near to the ileocecal valve, causing a 12 cm long intussusception with moderate ischemic damage. Conclusion. Colonic obstruction due to intussusception caused by lipomas is a very rare condition that needs urgent treatment. CT is the radiologic modality of choice for diagnosis (sensitivity 80%, specificity near 100%); since the majority of colonic intussusceptions are caused by primary adenocarcinoma, if the etiology is uncertain, the lesion must be interpreted as malignant and extensive resection is recommended. At present, surgery is the treatment of choice and determines an excellent outcome.